Proposição e teste de um modelo para avaliação da qualidade percebida e das atitudes e intenções comportamentais de consumidores de restaurantes à la carte - Barbosa, Álvaro Alexandre da Silveira (2016)
The aim of this study is to understand the post purchase behavior of college consumers at night à la carte restaurants in Lavras, Minas Gerais. Therefore, the determining factors of perceived quality as well as of attitudes and behavioral intentions regarding college students is identified through a properly designed and validated scale during this research. Simultaneously, a model that would enable to understand how the constructs are related, whether confirming or not the related cause-effect hypothesis is proposed. A quantitative approach was employed as methodology, in which, structured formularies were applied on college students at campus, through non-probability sampling techniques for accessibility. Data were analyzed via descriptive statistics (frequency distribution) and multivariate statistical techniques (Structural equation modeling - SEM). Results showed that attendance, climate and environment, food properties and concern for customers were considered by a la carte restaurant consumers as the main quality aspects. Of the nine subdimensions proposed to explain the perceived quality only that of accessibility presents a median intensity effect, whereas the others had a great effect on its variance. Results also confirm a direct and positive impact of quality and perceived value on satisfaction, just as the price and quality have direct and significant effect on the perceived value. Direct influence of low / cheap prices on consumer satisfaction was not confirmed, however, the first one indirectly impacts the latter through the perceived value, similarly to Vieira (2014) and Wanderley (2012) findings. The satisfaction, in turn, has a strong causal relationship or high power of explanation concerning the positive and negative emotions contrarily to the latter one, as well as on the loyalty propensity and word of mouth communication. The contribution of this work can be evaluated according to two fronts, the first being of academic nature, through the development of a quality perception and attitudes and behavioral intentions in restaurants à la carte scale. The second front, of management character, enables managers to identify the needs of potential customers and develop marketing strategies to satisfy and possibly hold them loyal.